2017
DOI: 10.1128/aem.01522-17
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pretreatment-Independent Saccharifications of Xylan and Cellulose of Rice Straw by Bacterial Weak Lignin-Binding Xylanolytic and Cellulolytic Enzymes

Abstract: Complete utilization of carbohydrate fractions is one of the prerequisites for obtaining economically favorable lignocellulosic biomass conversion. This study shows that xylan in untreated rice straw was saccharified to xylose in one step without chemical pretreatment, yielding 58.2% of the theoretically maximum value by B-6 PcAxy43A, a weak lignin-binding trifunctional xylanolytic enzyme, endoxylanase/β-xylosidase/arabinoxylan arabinofuranohydrolase. Moreover, xylose yield from untreated rice straw was enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…While lignin is the most universally recognized cause of recalcitrance, the importance of other biomass components has been increasingly reported [3236]. For instance, several studies have shown that removing xylan increases the porosity of the biomass and results in higher conversion of cellulose during saccharification [3741]. Hydroxycinnamic acids, ferulic acid (FA) and p -coumaric acid (CA) [23, 42, 43] and lignin composition (S/G ratio) [31, 44, 45] are other factors that have been implicated in influencing recalcitrance because they affect the strength and abundance of the cross-links between lignin and xylan [10, 46].…”
Section: Introductionmentioning
confidence: 99%
“…While lignin is the most universally recognized cause of recalcitrance, the importance of other biomass components has been increasingly reported [3236]. For instance, several studies have shown that removing xylan increases the porosity of the biomass and results in higher conversion of cellulose during saccharification [3741]. Hydroxycinnamic acids, ferulic acid (FA) and p -coumaric acid (CA) [23, 42, 43] and lignin composition (S/G ratio) [31, 44, 45] are other factors that have been implicated in influencing recalcitrance because they affect the strength and abundance of the cross-links between lignin and xylan [10, 46].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cassava pulp degrading enzyme of C. manihotivorum CT4 T may be active and low binding to lignin in cassava pulp. Teeravivattanakit et al (Teeravivattanakit et al, 2017) reported that because the bacterial multifunctional enzyme PcAxy43A from Paenibacillus curdlanolyticus B-6 was a weak lignin-binding enzyme, this enzyme was capable of converting xylan contained in agricultural residues to xylose in one step without chemical pretreatment to remove lignin. Therefore, a weak lignin-binding enzyme is a potential factor for obtaining enzymes suitable for the hydrolysis of lignocellulosic materials (Berlin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PcAxy43A produced mainly xylose, but it did not produce arabinose, in which arabinose is one component of arabinoxylan of corn hull. This may be because the arabinose in arabinoxylan of corn hull is linked to lignin and/or cellulose [7]. Teeravivattanakit et al [13] also found that the trifunctional xylanolytic enzyme, PxAxy43A, has the ability to hydrolyze xylan in rice straw to xylose in one step.…”
Section: Production Of Xylose From Corn Hull By Pcaxy43amentioning
confidence: 99%